Palynology, Stratigraphy and Geometry of the Pennsylvanian continental Santa Susana Basin (SW Portugal) - Machado, G.; Dias da Silva, I.; Almeida, P. (Journal of Iberian Geology, 2012)
The continental Pennsylvanian Santa Susana Basin (SSB) is located along an important N-S strike shear zone (Santa Susana Shear Zone - SSSZ) that separates the Ossa-Morena and South Portuguese Zones (SW Portugal). This shear zone controlled the sedimentation of the basin and probably its post-sedimentary evolution. The lower (basal) unit is mostly conglomeratic and is known essentially from drill-hole data while the upper unit, that covers most of the current surface area, is composed by sandstones, shales and some coal beds. Fluvial sedimentary rocks seem to prevail, but evidences of lacustrine sedimentation can be found in restricted areas within the upper unit. Palynological data indicate that at least part of the sedimentation took place during the Early Kasimovian (Cantabrian) but the sporomorph content of different localities suggest that significantly older sediments (Late Moscovian -Early Bashkirian) may be present. Geometrical, structural, and cartographical evidences indicate that the SSB formed as a pull-apart basin along the SSSZ and was later partially uplifted during latest Varsican and Alpine orogenies.>